Kupipakwa Rasayan In Ayurveda: Traditional Method And Its Modern Relevance – A Critical Review Study - Nirgude Prashanti Babarao (Ayurline: International Journal of Research in Indian Medicine, 2025)
To critically analyze traditional Kupipakwa Rasayan preparation methods and evaluate their relevance and adaptation in contemporary pharmaceutical practice [1–5]. Objectives: Describe classical methodology of Kupipakwa Rasayan: Poorva Karma, Pradhana Karma, Paschat Karma [6–10]. Examine traditional parameters for controlled heating (Kramagni) and final product classification (Kanthastha, Talastha, Ubhayastha) [11–15]. Correlate classical methods with modern analytical techniques for reproducibility, safety, and efficacy [16–20]. Explore therapeutic significance in contemporary medicine [21–25]. Observations: Purified mercury (Parada) and sulfur (Gandhaka) are triturated to form Kajjali and placed in a sealed glass vessel (Kupi) in a sand bath (Valuka Yantra). Controlled sequential heating (Kramagni) transforms the mixture into crystalline or sublimated products. Observations of color, fumes, flame, and Shalaka test guide process completion, supplemented by thermocouples and pyrometers for precise temperature regulation [21–25]. Results: Products show complete chemical transformation into therapeutically potent, stable compounds. Particle analysis demonstrates nano- to submicron sizes, enhancing bioavailability. Deposition patterns (Kanthastha, Talastha, Ubhayastha) are reproducible and align with classical therapeutic claims [26–30]. Conclusion: Kupipakwa Rasayan exemplifies integration of classical Ayurvedic wisdom with modern pharmaceutical science. Structured preparation combined with analytical validation ensures safe, reproducible, and clinically relevant formulations suitable for contemporary integrative medicine [1–30].